Pengaruh Keterlibatan Orang Tua pada Perkembangan Literasi Membaca Anak Sekolah Dasar - Amalia, Dini; R, Irayanti; Noorkhalisah, Noorkhalisah; Maisarah, Sri; Suriansyah, Ahmad; Rafianti, Wahdah Refia (Jurnal Cahaya Edukasi, 2025)
Reading literacy competence is an essential skill that plays a crucial role in supporting the academic achievement of elementary school students. However, low levels of reading literacy competence remain a common issue, partly due to the insufficient involvement of parents in fostering reading habits at home. This study aims to analyze the relationship between parental involvement and the development of reading literacy competence among elementary school children. This research employed a descriptive qualitative approach using a library research method. Data were collected from various relevant academic literature and analyzed by comparing findings from previous studies. The results indicate that active parental involvement significantly contributes to improvements in children’s reading ability, reading interest, learning motivation, self-confidence, and critical thinking skills. Forms of parental involvement include reading assistance, provision of reading materials, emotional support, and the creation of a conducive learning environment at home. Therefore, sustained collaboration between schools and families is essential in strengthening a culture of reading literacy from an early age.